Application of empathy map on educational actions carried out by nursing professionals - Cíntia Eliane Costa Corrêa; Giovana Puchalski Lopes; Caroline Barbosa da Silva; Julyhe Nunes Paulin; Nathália Dias Oliveira; Murilo dos Santos Graeff; Ana Amélia Antunes Lima; Adriana Aparecida Paz (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objective: to apply an empathy map to assess nursing professionals' needs, desires, frustrations and aspirations regarding educational actions. Methods: a cross-sectional study, carried out in a hospital institution with 164 nursing professionals, who responded to the empathy map, which clarified their participation in institutional educational actions, which were collected from 2019 to 2020, and analyzed using descriptive statistics. Results: when using the empathy map, educational actions focused on routines predominated, with the sharing of knowledge; promotion of improvements in care; agreement of commitment with proposed actions; insufficient compliance; little incentive to participate; dispersed guidelines among professionals; increased labor demand; and educational activity during the working day. Conclusions: the empathy map, applied as an instrument for assessing the institutional educational process, qualified as appropriate educational actions or opportunities to improve significant learning for professional nursing education.